The Impact of The Merdeka Curriculum on Indonesia Education - Daniel Pasaribu (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to determine the effect of the size of the independent curriculum on Indonesian education. This study is a type of SLR research and meta-analysis. This research data comes from an analysis of 10 national and international journals published in 2018-2023. The keyword for data search is the influence of the independent curriculum in Indonesia. Search data sources through google scholar databases, Educarion Resources Information Center (ERIC), and ScienceDirect. Data analysis with the help of Comprensive Meta-analysis (CMA) applications. The results of the study concluded that the independent curriculum has a positive effect on the education system in Indonesia with a summary effect size value (rE = 0.68; Z = 8.146; p < 0.001). This finding shows that the application of the mendeka curriculum has a significant effect on Indonesian education in the medium category. The implementation of an independent curriculum can train students to have critical thinking skills, scientific literacy and student numeracy in learning.